Production and nutritional quality of corn under rainfed conditions in Aguascalientes, Mexico - Flores Ancira, Ernesto; Díaz Romo, Abraham; Haubi Segura, Carlos; López Gutiérrez, Mario Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
In Aguascalientes, during 2014-2016, the production of grain and stubble and the nutritional quality of maize during 2014-2015 was evaluated, cultivated under dry conditions in the municipalities of El Llano (LL) and Rincón de Romos (RR). The production (grain + stubble) was 2 413, 1 072 and 2 059 kg ha-1 and 699, 318 and 483 kg ha-1 for El Llano and Rincón de Romos, during 2104, 2015, and 2016 respectively. The stubble in LL resulted with 2 113, 969 and 1 856 kg ha-1, against 419, 191 and 290 kg ha-1 obtained in RR for the years 2014, 2015, and 2016 correspondingly. The grain production was 299, 103, and 201 kg ha-1, against 280, 127 and 193 kg ha-1 for the same municipalities and years reciprocally. The crude protein was similar (p≥ 0.05) in 2014 with 6.7 and 6.2% and different (p≤ 0.05) in 2015 with 5.3 and 2.9%, for the same municipalities. Neutral detergent fiber was similar (p≥ 0.05) with 55.8 and 56.6%, and 61.4, 65.2%, for RR and LL during 2014 and 2015 respectively. The acid detergent fiber differed (p≤ 0.05) from 30.9 and 30.2% and 34.6 and 38.3% during the years 2014 and 2015 in RR and LL respectively. The adjusted in situ digestibility curves of the dry matter were similar (p≥ 0.05) in the two RR and LL locations, and the 2014 and 2015 evaluation periods.